(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: To describe the current situation of cyberbullying and coping strategies among students of Hanoi Medical University in the academic year 2023-2024. Method: A cross-sectional study was conducted at Hanoi Medical University from July 2023 to April 2024 with 513 students. Data was collected through a self-administered questionnaire, assessed using the Cyberbullying Scale. Results: The average time spent on social media was 5.59 hours per day, primarily in the evening. Facebook and TikTok were the most popular platforms. The rate of students experiencing cyberbullying was relatively low, but some students still encountered negative behaviors. The most common coping method was sharing information and seeking advice from friends. Although the rate of bullying was not high, the negative impact on mental health remained a significant concern. Conclusions: Universities need to pay attention and implement measures to protect students from the risks of cyberbullying.